PERTANGGUNGJAWABAN PIDANA BAGI PARA PELAKU DOXING MENURUT UU ITE DAN UU PDP - Muhammad Arvy Chico Armando; Hari Soeskandi (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
This research will discuss Doxing, which is an internet crime that is committed by collecting someone's personal data. Then this personal data will be disseminated to intimidate the target. Victims of doxing are generally journalists, politicians, activist groups, and ordinary people. The purpose of doxing is to silence someone and sometimes just for fun. This study uses a normative juridical method, with inventory techniques and analyzes in secondary data consisting of primary legal materials and secondary legal materials with the technique of understanding the law as a guide in a legislation that regulates doxing whose aim is to find legal principles, rules -rule of law, and legal doctrine aim to provide answers in solving legal issues that have been researched. By using this concept, researchers want to explain criminal penalties for doxing perpetrators according to applicable regulations. So as to be able to provide answers regarding the research study being studied